About prefix -ba in Minangkabaunese: from which the study should start - Jufrizal Jufrizal (Politeknik Negeri Bali, 2018)
The four layers of human language – form, meaning, function, and value – are systematically integrated in order to play the communicative functions of human interaction. It is not an easy job to explore and to explain the nature of human language as the four layers are systematically integrated in complex ways. Thus, the linguistic studies should be held in specific domains and topics by means of appropriate theoretical bases and frameworks. This paper, which is mainly inspired by the grammatical-typological analysis on prefix ba- in Minangkabaunese, particularly discusses how the language features are linguistically analyzed in order to come to logic, valid, reliable findings and conclusion. The discussion presented in this paper aims at proposing logical and reasonable ways of doing linguistic analyses on available data of language. In short, this paper deals with how to begin and to do linguistic analyses toward a group of language data collected. In this paper, the prefix ba- of Minangkabaunese is used as the example of case. The discussion presented in this paper respectively answers two main questions; (i) What should be firstly analyzed dealing with the prefix ba- of Minangkabaunese?; and (ii) How are the linguistic analyses toward the prefix ba- of Minangkabaunese logically continued?